Da'wah of the Muhammadiyah Student Association in Tanggulangin District during the Covid 19 Pandemic - Gebriela Palomargareta; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The Covid-19 pandemic has changed our daily activities in all aspects, including the organizational field. One of the organizations is the Muhammadiyah Student Association organization located in Tangulangin. This study’s goal is to identify the form of da'wah who carried out by the Muhammadiyah Student Association organization Tanggulangin during the Covid-19 pandemic. This study uses a combination of qualitative and quantitative (mixed methods) with using data collection techniques through interviews and observations. The results showed that organizational activities during the pandemic continued even though there were many obstacles, but other activities continued to run by adjusting the situation and conditions during the pandemic in realizing these activities.